University Faculty’s Perspectives on the Roles of E-Instructors and Their Online Instruction Practice - Chang, Chiungsui; Shen, Hun-Yi; Liu, Eric Zhi-Feng (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
Despite the rapid use of e-Learning in higher education, the beliefs of instructors about and their practices during online instruction have been seldom addressed. This study explores the role perceptions of e-instructors in higher education. In total, 106 instructors from 20 Taiwanese universities filled out a questionnaire. Analytical results indicate that “content expertise” and “instructional designer” are perceived by university faculty as the key components in e-instruction in higher education. A gap exists between ideal and practical roles of e-instructors in higher education. Role perceptions and role-based practices of e-instructors in higher education differ significantly in terms of gender and teaching experience. This study also provides suggestions for e-instructor training.